Astaxanthin attenuated pressure overload-induced cardiac dysfunction and myocardial fibrosis: Partially by activating SIRT1 - Zhang, Jun; Wang, Quan-zhen; Zhao, Shao-hua; Ji, Xiang; Qiu, Jie; Wang, Jian; Zhou, Yi; Cai, Qian; Zhang, Jie; Gao, Hai-qing (Biochimica et biophysica acta. General subjects, 2017)
Myocardial fibrosis contributes to cardiac dysfunction. Astaxanthin (AST), a member of the carotenoid family, is a well-known antioxidant, but its effect on and underlying mechanisms in myocardial fibrosis are poorly understood. In vivo, myocardial fibrosis and cardiac dysfunction were induced using transverse aortic constriction (TAC). AST was administered to mice for 12weeks post-surgery. In vitro, transforming growth factor β1 (TGF-β1) was used to stimulate human cardiac fibroblasts (HCFs). EX-527 (6-chloro-2, 3, 4, 9-tetrahydro-1H-carbazole-1-carboxamide) and SIRT1 siRNA were used to inhibit SIRT1 in vivo and in vitro, respectively. The effects of AST on cardiac function and fibrosis were determined. SIRT1 expression and activity were measured to explore the mechanisms underlying its effects. AST improved cardiac function and attenuated fibrosis. Receptor activated-SMADs (R-SMADs), including SMAD2 and SMAD3, played important roles in these processes. The TAC surgery-induced increases in the expression of phosphorylated and acetylated R-SMADs were attenuated by treatment with AST, the translocation and transcriptional activity of R-SMADs were also restrained. These effects were accompanied by an increase in the expression and activity of SIRT1. Inhibiting SIRT1 attenuated the acetylation and transcriptional activity of R-SMADs, but not their phosphorylation and translocation. Our data demonstrate that AST improves cardiac function and attenuates fibrosis by decreasing phosphorylation and deacetylation of R-SMADs. SIRT1 contributes to AST’s protective function by reducing acetylation of R-SMADs. These data suggest that AST may be useful as a preventive/therapeutic agent for cardiac dysfunction and myocardial fibrosis. •Astaxanthin mitigated TAC-induced cardiac dysfunction and myocardial fibrosis.•Astaxanthin reduced R-SMAD phosphorylation and acetylation.•Astaxanthin attenuated the translocation and transcriptional activity of R-SMAD.•SIRT1 contributed to the protective function of Astaxanthin.